Geochemical study of groundwater conditions with special emphasis on fluoride concentration, Iran. Issue 47 (7th October 2016) - Biglari, Hamed; Chavoshani, Afsaneh; Javan, Nasibeh; Hossein Mahvi, Amir
Abstract: The quality of groundwater at any point below the surface shows the combined effects of many processes in the groundwater flow path. Factors of chemical reactions such as precipitation, weathering, dissolution, ion exchange, and various biological processes commonly happen below the surface, influencing fluoride concentrations in groundwater. Due to the fluoride effects on human health and the fact that few studies have been conducted on the factors affecting low fluoride amounts, these factors were investigated in Sistan and Baluchestan province, Iran. Water samples from 270 open dug wells, located in nine cities, were collected within 10 years (from 2004 to 2014). They were analyzed for major ions according to the standard methods. In this study, parameters such as pH, specific electrical conductivity, temperature, total dissolved solids, sulfate, nitrate, fluoride, total alkalinity, total hardness, carbonate, bicarbonate, magnesium, calcium, sodium, and potassium were analyzed. It was revealed that the soil was saline with natural pH. The fluoride amount in groundwater was deeply influenced by the composite of granitic, NaF, and CaF2 rocks for a prolonged period. The wells showed many changes of fluoride concentration from 0.125 to 1.71 mg/l and fluoride decreased toward the Southeast. Na +, Ca +, Cl −, and along with F showed a positive correlation; however, plots in comparison with F showed a negative correlation. Obtained results from this study indicate that the hydrological condition of groundwater is also an important factor controlling the amount of fluoride in groundwater.